Reliability of complex timber structures: impact of connection non-linearity and overstrength - Caprio, Dorotea; Jockwer, Robert; ICASP14 (My University, 2023)
In statically indeterminate timber structures, the stiffness of the members and the semi-rigid behavior of the joints influence the force distribution in the structure, affecting its performance and reliability. In this paper the impact of the non-linear load-deformation behavior of connection on a simple statically indeterminate timber structure is evaluated. The basis of the definition of the non-linear load-deformation behavior of connections in terms of stiffness, load-carrying capacity, and ductility is reviewed. The reliability of a beam supported by rotational spring is determined in a Monte-Carlo analysis. The impact of different typical variation of the connection design as well as overstrength and excessive stiffness are evaluated. It is shown that by considering sufficient ductility of the joints a gain in reliability of structural indeterminate structures compared to the reference condition of a simply supported beam can be achieved. More detailed specifications on how to consider the connection non-linearity in design should be introduced in design codes.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED